2019
DOI: 10.7150/jca.27779
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumour size on metastasis and survival in patients with pancreatic neuroendocrine tumours (PNETs): A population based study

Abstract: Background: The relationship between tumour size and metastasis rate is poorly recognized in patients with pancreatic neuroendocrine tumours (PNETs). The impact of tumour size on prognosis was controversial in previous investigations.Methods: PNETs cases diagnosed from 1988 to 2013 were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database. Clinicopathologic features were retrospectively analyzed. Survival was calculated by the Kaplan-Meier method. Multivariable Cox regression models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Tumor size affects the possibility of metastasis [ 16 ]. According to the European Neuroendocrine Oncology Society standards, 2 and 4 cm were considered to be important thresholds affecting the prognosis in pNEN patient [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size affects the possibility of metastasis [ 16 ]. According to the European Neuroendocrine Oncology Society standards, 2 and 4 cm were considered to be important thresholds affecting the prognosis in pNEN patient [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] Moreover, in clinical practice, increasing tumor size affects the probability of metastasis in patients with neuroendocrine pancreatic cancer. [ 32 ] A significant relationship between tumor dimension and metastasis was also found in patients with stage IV non‐small lung carcinoma. [ 33 ] In addition, the biological factors involved in the metastatic initiation process are not necessarily expressed by all cells originating from the primary tumor site.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery represents the optimal therapeutic approach for pancreatic neuroendocrine tumors, with the surgical strategy for NF-pNETs primarily contingent upon tumor size and histological grading. It has been shown that smaller NF-pNETs also have some malignant potential [21], and aggressive surgery can improve the prognosis of patients [22]. In the study conducted by Shi et al, surgical intervention signi cantly enhanced patient prognosis, resulting in a more than 60% reduction in mortality risk for both younger and older individuals [23].…”
Section: Discussionmentioning
confidence: 99%